PENERAPAN SISTEM INFORMASI PENJUALAN PADA UKM BILQIS DI DESA SANROBONE KECAMATAN SANROBONE KAB. TAKALAR - Dolly Indra; Ihwana As’ad (Universitas Indraprasta PGRI, 2022)
SMEs are a type of business that is carried out on a small to medium scale. Bilqis UKM is located in Sanrobone Village, Takalar Regency that focuses on sales, namely school clothes, and uniforms where sales are still conventional. With the rapid development of information technology today, we implement a website-based information system for UKM Bilqis as an online sales medium. In this service, we provide assistance in the use of sales information systems both from shop owners in this case Bilqis UKM, and from buyers taken from random samples. The results in this service are a questionnaire used for application assessment that we made with the result was good.